Callus induction and somatic embryogenesis in Stevia rebaudiana Bertoni as a medicinal plant - Keshvari, Tahereh; Najaphy, Abdollah; Kahrizi, Danial; Zebarjadi, Alireza (Cellular and Molecular Biology, 2018)
Stevia rebaudiana (Bert.) from Asteraceae family is a useful medicinal plant that prevents and cures diabetes, blood pressure, weight gain and tooth decay. Due to self-incompatibility in stevia, somatic embryo investigation for artificial seed production is valuable in this plant. In order to evaluate the callus induction characteristics in stevia, a factorial experiment was laid out based on a completely randomized design with three replications. The factors included ten hormone combinations and control, two kinds of media (MS and B5) and two types of explants (leaf and internode). Callus induction characters including the percentage of callus formation, days to callus induction, fresh and dry callus weight were recorded. Analysis of variance showed significant differences (p<0.01) among hormone combinations, media and explant types as well as their interactions. The best treatment for callus induction with minimum time to callus formation was 1 mg/l NAA+1 mg/l BAP. The highest fresh and dry callus weight were obtained on B5 medium supplemented by 1 mg/l 2,4-D+1 mg/l BAP (in leaf explant) and 0.25 mg/l 2,4-D+ 0.1 mg/l BAP (in internode explant). These results can be used in suspension culture. To induce somatic embryogenesis in suspension culture, six hormone treatments were investigated. The highest somatic embryogenesis percentage was obtained in MS medium supplemented by 2 mg/l 2,4-D+ 0.5 mg/l NAA+0.5 mg/l BAP.